Power in Centralized Education Systems: Teachers’ Perspectives in Egypt - Ali, Mona (2016)
The main purpose of this dissertation is to examine the concept and practice of power. The research explores definitions of power with a special reference to the centralized system of governance. Moreover, the research explores the concept of accountability as a key means in the relation between power and autonomy. The research was conducted by taking multi perspective approach within a qualitative research study to explore the case of Egypt as an example of a centralized system. Research methods employed include piloting, semi-structured interviews with six teachers, and documents study. The findings show a number of contradictions between the rhetoric used by the Ministry of Education and its practices with teachers and schools. The study also shows that the Ministry’s use of the language of freedom is a means to cover the repression that it practices to maintain its power. Also, the results suggest that the Ministry’s practicing high levels of accountability on teachers does not entirely take away their autonomy.